Effect of educational intervention on knowledge, attitude and practice of hepatitis B vaccine among medical students - A. V., Sareetha; H., Nagabushan; K. H., Supriya (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Aim of the study were to assess the impact of education on knowledge, attitude and practice of Hepatitis B vaccine among medical students and to educate the students regarding Hepatitis B vaccination. Methods: Non-randomized before and after comparison study was conducted to evaluate changes in knowledge, attitude and practice of Hepatitis B vaccination (HBV), assigning structured questionnaire of 26 different statements concerning knowledge, attitude and practice by pre and post educational intervention on Hepatitis B and its vaccination. Results: The study was conducted among 100 second year medical students. The response rate was 100%. There was statistically significant improvement in knowledge from pre-test mean scores for modes of transmission (87.4+4.70 vs 95.8+1.61; p=0.0001), preventive measures (92+0.47 vs 98+0.94; p=0.001) and Hepatitis B vaccine (71+4.72 to 84.7+6.65; p=0.0001) to post-test. While the increase in mean scores from pre-test for attitude (68.6+9.21 vs 77.43+11.1) and practice (55+25.41 vs 65.6+32.6) were statistically significant in post-test (p=0.0001; p=0.001 respectively). Conclusions: Structured educational intervention among medical students about Hepatitis B vaccination showed improved knowledge and behaviour and also increased the percentage of students willing to get screened and their participation in health education programmes related to Hepatitis B. However, there is slight lack of knowledge regarding the transmission of Hepatitis B and its vaccination schedule. In this regard, implementation and evaluation of educational intervention is needed as a preventative measure.